Geographic and temporal comparison of skulls of striped dolphins off the Pacific coast of Japan - Amano, Masao; Itto, Haruka; Miyazaki, Nobuyuki (J. Cetacean Res. Manage., 2000)
Skulls of striped dolphins taken by the drive fishery off the Pacific coast of Japan in 1958-79 and 1992, and those taken by research vessels in offshore waters of the northwestern North Pacific in 1992 were examined to study the geographic and temporal differences that are expected to suggest the identity of stocks exploited by the fishery. Coastal specimens collected in 1958-79 showed distinct sexual dimorphism in rostral width, while no dimorphism was found in recent (1992) coastal specimens. Females showed more obvious variation among samples, and recent coastal specimens were distinct from others. The present results provide some support for the view that the drive fishery has exploited dolphins from plural coastal stocks, and that coastal dolphins currently taken by the Taiji fishery and offshore dolphins ranging east of 145°E do not belong to the same stock. The need to obtain larger sample sizes is stressed.